The Role of the Creative Economy in Enhancing the Competitiveness of Traditional Herbal SMEs: A Mediation Analysis of Innovation Capability - Ayuk Setiyawan; Fida' Husain; Aulia Uswatun Khasanah; Aulia Galuh Ani Sekar Arum; Nofia Fajar Ramahdan (Universitas Muhammadiyah Surakarta, 2026)
The rapid development of the creative economy requires traditional herbal small and medium enterprises (SMEs) to improve their competitiveness. However, many herbal SMEs still face challenges in innovation, packaging, and marketing. This study aims to analyze how strengthening innovation capability can enhance the competitiveness of traditional herbal SMEs. The research employed a quantitative approach using a survey of 70 traditional herbal SME owners and managers. Data were analyzed using descriptive statistics, reliability and validity testing, correlation analysis, path analysis, and mediation analysis. The results show that digital media, storytelling, and collaboration positively influence innovation capability, while product innovation has a negative effect. Furthermore, innovation capability strongly mediates the relationship between creative economy elements and competitiveness, with digital media being the most dominant factor. These findings highlight the importance of digital literacy, collaboration, and authentic product narratives in strengthening the competitiveness of traditional herbal SMEs.